The contribution of physical education and sports to improving the mental and physical health of secondary school students (Aged 15–18) - Eddine, Medani Djamel; Sadi, Mohammed Sadi; Zeraoula, Ali; Ilyas, Satour; Abdelkader, Boutaloula (The International tax journal, 2025)
This study aims to identify the extent to which physical education and sports classes contribute to the achievement of certain health dimensions, such as physical fitness and mental health, among secondary school students. The sample comprises 22 teachers, and a descriptive analytical method was adopted. We used a 30-item questionnaire, with 15 items for each dimension, as the study tool. We used SPSS statistical software. The results of the study showed the following: Physical education and sports classes contribute to achieving certain health dimensions among secondary school students, Physical education and sports classes enhance physical fitness among secondary school students, Physical education and sports classes promote mental health among secondary school students.